The Impact of the Odd-One-Out Strategy on the Achievement of Fifth-Grade Literary Female Students in the Subject of Principles of Philosophy and Psychology - Saja Hasan Hadi; Dr. Fuad Ali Farhan (Migration Letters, 2023)
The aim of this research is to determine the impact of the "exotic item extraction" strategy on the academic achievement of fifth-grade literary female students in the subject of Principles of Philosophy and Psychology. To achieve this research objective, the following null hypothesis was formulated: "There is no statistically significant difference at the 0.05 level between the average academic achievement scores of the experimental group, who study using the exotic item extraction strategy, and the average academic achievement scores of the control group, who study using the traditional method, for fifth-grade literary female students in the subject of Principles of Philosophy and Psychology." The research sample was randomly selected from Al-Huda Girls’ Preparatory School within the Tarmiya district of the Directorate of Education in Baghdad, Al-Karkh Third. Using random sampling, the experimental and control groups were selected from fifth-grade literary female students at Al-Huda Girls’ Preparatory School. The experimental group consisted of 25 students from section (B), who studied Principles of Philosophy and Psychology using the exotic item extraction strategy. The control group consisted of 25 students from section (A), who studied Principles of Philosophy and Psychology using the traditional method. The researcher adopted a two-group experimental design with pretest-posttest self-report. To test the research hypothesis, a achievement test was developed to obtain the required data. After consulting with teachers and experts, the test consisted of 40 multiple-choice items. This test was chosen for its ease of scoring, comprehensive coverage of the subject matter, quick response from students, and statistical accuracy of results. The researcher began implementing the experiment on Tuesday, February 21, 2023, and concluded it on Thursday, April 20, 2023. Both groups received two classes per week. Thus, the duration of the experiment was equal and consistent for the students in both study groups. The researcher also personally taught both the control and experimental groups to ensure objectivity in teaching and to avoid the influence of external variables that could affect the accuracy of the experiment’s results. The researcher utilized the SPSS statistical software package for the social sciences to analyze the data statistically, using t-tests, chi-square, difficulty and discrimination indices, alternative item effectiveness, and the Kuder-Richardson 20 equation. After completing the experiment, the results of the statistical analysis showed that the experimental group outperformed the control group in academic achievement. Therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted, which states: "There is a difference in academic achievement." Statistical significance was found at the (0.05) level in academic achievement, with a significant difference between the mean scores of the experimental group and the control group, in favor of the experimental group that studied using the exotic item extraction strategy. Based on the results, the researcher made several recommendations and subsequently proposed suggestions.